2017
DOI: 10.1002/jat.3435
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of drug‐induced liver injury using keratinocytes

Abstract: Drug-induced liver injury (DILI) is one of the most common adverse drug reactions. DILI is often accompanied by skin reactions, including rash and pruritus. However, it is still unknown whether DILI-associated genes such as S100 calcium-binding protein A and interleukin (IL)-1β are involved in drug-induced skin toxicity. In the present study, most of the tested hepatotoxic drugs such as pioglitazone and diclofenac induced DILI-associated genes in human and mouse keratinocytes. Keratinocytes of mice at higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The keratinocytes used in this study were prepared as previously described ( 63 ), with minor modifications. Skin tissue was isolated from 1- or 2-day-old mice and incubated for 15–18 h at 4 ° C in CnT-PR medium (CELLnTEC; Bern, Switzerland) supplemented with antibiotic–antimycotic mixed solution and 5 mg/mL dispase (Wako Pure Chemical, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The keratinocytes used in this study were prepared as previously described ( 63 ), with minor modifications. Skin tissue was isolated from 1- or 2-day-old mice and incubated for 15–18 h at 4 ° C in CnT-PR medium (CELLnTEC; Bern, Switzerland) supplemented with antibiotic–antimycotic mixed solution and 5 mg/mL dispase (Wako Pure Chemical, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Different hepatotoxic compounds have been shown to induce the expression of genes related to the immune and inflammatory response, such as S100A8, S100A9, NALP3, IL-1 β and RAGE in both hepatocytes 417 and primary human keratinocytes 418 . Furthermore, it has been observed that the basal expression and induction of IL-1 β in keratinocytes after exposure to hepatotoxic drugs can be a tool to identify individuals at high risk of iDILI 418 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The use of patient-derived keratinocytes would also be an interesting approach to identify risk factors associated with liver injury related to immune-mediated cutaneous reactions [66]. Recent data suggest that DILI-associated genes are involved in the onset and progression of drug-induced skin toxicity and keratinocytes and hepatocytes may share similar responsiveness to hepatotoxic drugs [67].…”
Section: Causality Assessment Scales Strengths Limitationsmentioning
confidence: 99%